PENGARUH KONSENTRASI HOMOGENAT JAMUR Pythium aphanidermatum (Edson) Fitzp terhadap Kandungan Ajmalisin dalam Kultur Agregat Sel Catharanthus roseus (L.) G. Don - Asra, Revis (PMIPA FKIP UNJA, 2021)
An experiment on the effect of elicitor concentrations derived from Pythium aphanidermatum (Edson) Fitzp on ajmalicine content of Catharanthus roseus (L.) G. Don Cell aggregates culture has been conducted. The following concentrations of elicitor tested were 0.05; 0.5; 1.0 and 5.0 mg DW/mL. The harvesting times were 0; 18; 36 and 72 hours after elicitation. The ajmalicine was analyzed qualitatively and quantitavely by using High Performance Liquid Chromatography (HPLC). Ajmalicine content was influenced by the concentration of elicitor and harvesting time. The highest content of ajmalicine in the cell aggregates (13.089 ± 0.086 µg/gDW) was achieved by addition 1.0 mg DW/mL of elicitor after 18 hours whilts in the medium (346.728 ± 2.843 µg/gDW) was achieved by addition 1.0 mg DW/mL of elicitor after 36 hours Kata kunci: Catharanthus roseus (L.) G . Don, Phytium aphanidermatum, elisitor, ajmalisin